#### Question

Use the Remainder Theorem to find which of the following is a factor of 2x^{3} + 3x^{2} – 5x – 6.

x + 1

#### Solution

By remainder theorem we know that when a polynomial f (x) is divided by x – a, then the remainder is f(a)

let `f(x)=2x^3+3x^2-5x-6`

`f(-1)=2(-1)^3+3(-1)^2-5(-1)-6=-2+3+5=0`

Thus, (x + 1) is a factor of the polynomial f(x).

Is there an error in this question or solution?

Solution Use the Remainder Theorem to Find Which of the Following is a Factor of 2x3 + 3x2 – 5x – 6. X + 1 Concept: Remainder Theorem.